Simulation of LM6 alloy with Ti-B refinement in squeeze casting process - Mona Kiaee, (2015)
Squeeze casting is a technique of casting which comes with the advantage of making casting products almost without porosity. It combines the advantages of casting and forging process and results in higher quality of products compare to the conventional casting techniques. Squeeze casting is widely used to produce quality casting of light materials such as magnesium or aluminum alloys. In this study, simulation of Finite Difference Method (FDM) was used to investigate the effect of die pre heat temperature and melt temperature on mechanical properties of squeeze cast aluminium alloy. The common defects of squeeze casting process and solidification on Al-Si alloys were also investigated. This study included three sections; the first set of simulation was to compare and verified the results with an experimental work on gravity die casting of aluminium-11.8% silicon alloy and Ti-B as a refinement. In the second section of this research, effect of squeeze casting process parameters on tensile strength, hardness and elongation was studied. In the final section, obtained results from first two sections were used to simulate a complex shape product of squeeze cast aluminium-11.8% silicon with Ti-B refinement. This section was to study the effects of squeeze casting parameters on microstructural and mechanical properties of Al-Si alloys. The common defects of air entrapment and air pressure were also investigated.